Tradition, identity and representation in Anshun Dixi opera of the Tunpu Community, Guizhou, China - Wu, Heng (2024)
Anshun Dixi is a traditional opera popular in the Tunpu Community, Anshun City, Guizhou Province, China. According to the classification system of Chinese opera, the operatic identity of Anshun Dixi is still controversial. The Tunpu people have consistently upheld the custom of engaging in Dixi performances, highlighting the essential significance that Dixi plays in the military identity and the immigrant identity of the Tunpu community. This study aims to examine the operatic identity and musical meaning of Anshun Dixi. The concept of “great tradition and little tradition”, Bohlman’s (2005) proposition of “music as a representation”, and the “intertextuality” theory of Kristeva (1969) and Tokumaru (2000) are adopted as discourse. Anshun Dixi’s operatic identity is analyzed within its musical framework and intertextual connection with several other operatic traditions in China. To investigate the musical representation of Anshun Dixi, a functioning network is constructed to connect music and non-musical components. Based on an ethnomusicology approach, this study carried out a field survey for three years in nine Tunpu communities, including Tianlong Village, Jiuxi Village, Fanhua Village, Guojiatun Village, Wuguan Village, Xinshao Village, Xiaojia Village, Xiayuan Village, and Zhouguan Village, spanning from 2021 to 2023. A series of representational symbols about the Tunpu context, ritual activities, opera performances, music texts, costumes and props, and dance movements were collected through field observation, audio and video recording. The relationship and significance of many symbols were elucidated through the specialized methods of music analysis, textual analysis, and performance analysis. By establishing an interactive network with a central focus on music, the connection between music and non-musical categories and the role of music in Dixi was examined. Furthermore, the operatic identity of Anshun Dixi is explored through the intertextual approach, which links Dixi to other Chinese operas and performing arts. The research findings indicate that Anshun Dixi is the product of the combined influence of several cultural components. The ritual part absorbs elements from the opera component, while the opera component does not encompass elements of rituals. Specifically, the opera segment does not serve as an offering to amuse the deities. However, its programmatic and virtual nature is flexible and does not adhere to the conventions of appreciative opera. Therefore, Anshun Dixi is a loose, unofficial, both ritualistic and appreciative folk opera. Despite being a ‘little tradition’, Anshun Dixi encompasses great elements. Music plays a central role in Anshun Dixi, as it combines different structural elements. The representation of music beyond itself reflects the divinity, military nature, immigrant status, and spirit of loyalty, righteousness, and bravery, which are related to the representation of Anshun Dixi. Furthermore, the music of Dixi also represents the uniqueness of sound, structure, and signs, which is the self-identity of music. In conclusion, while Anshun Dixi may be considered a folk tradition only transmitted among the Tunpu groups, for the community, Anshun Dixi serves as a representation of their culture.